Determination of correlation between cytokines IL 6, IL8, IL10, IL12, IL17 and severity of hepatocellular carcinoma in patients having hepatitis C - Ishtiaq Ahmad; Hamidullah; Ashraf; Murad Ali; Manzoor Hussain; Rehman Ud Din (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the correlation between the levels of interleukins 6, 8, 10, 12 and 17 and the severity of hepatocellular carcinoma in patients positive for hepatitis C. Method: The retrospective, cross-sectional, analytical study was conducted at the Department of Medicine, Mardan Medical Complex, Mardan, Khyber Pakhtunkhwa, Pakistan, and comprised data of hepatocellular carcinoma patients who were positive for hepatitis C on polymerase chain reaction test from March 2021 to December 2022. A control group of healthy patients was also included. The severity of hepatocellular carcinoma was assessed using the Barcelona Clinic Liver Cancer method, and the patients were classified into five stages: very early stage 0, early-stage A, intermediate-stage B, advanced-stage C, and end-stage D. Interleukin 6, 8, 10, 12 and 17 levels and disease severity were correlated using Pearson correlation coefficient. Data was analysed using SPSS 26. Results: Of the 115 subjects, 67(58.3%) were patients and 48(41.7%) were controls. There were 72(62.6%) males and 43(37.4%) females. The median age of patients was 56 years (interquartile range: 38-64 years), and among the cases it was 36 years (interquartile range: 32-44 years). Among the patients, 8(11.94%) were at stage 0, 11(16.41%) stage A, 24(35.82%) stage B, 13(19.40%) stage C, and 11(16.41%) stage D. Intergroup differences indicated a significant difference, with interleukin levels being higher in patients with more advanced stages (p<0.05). Conclusion: The use of interleukin levels as biomarkers could facilitate earlier detection of advanced-stage disease, leading to more timely interventions and potentially improving patient outcomes. Key Words: Interleukins, Hepatitis C, Hepatocellular carcinoma, Cytokines.